2019
DOI: 10.1093/bioinformatics/btz699
|View full text |Cite
|
Sign up to set email alerts
|

Protein–protein interaction site prediction through combining local and global features with deep neural networks

Abstract: Motivation Protein–protein interactions (PPIs) play important roles in many biological processes. Conventional biological experiments for identifying PPI sites are costly and time-consuming. Thus, many computational approaches have been proposed to predict PPI sites. Existing computational methods usually use local contextual features to predict PPI sites. Actually, global features of protein sequences are critical for PPI site prediction. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
253
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(255 citation statements)
references
References 42 publications
2
253
0
Order By: Relevance
“…It can be found that the values of six measures achieved in these three independent benchmark datasets are lower than that in the dataset used in this work, but it is reasonable because the IHT-XGB model is built on this original dataset. Table 4 also shows the prediction performance of five models, i.e., SSWRF, LORIS, PSIVER, SCRIBER, and DELPHI, in identification of protein-protein interaction sites [31][32][33][34][35][36][37]. The highest results in each performance measures for different models are highlighted as bold type.…”
Section: Prediction Performance In Independent Benchmark Datasetsmentioning
confidence: 99%
“…It can be found that the values of six measures achieved in these three independent benchmark datasets are lower than that in the dataset used in this work, but it is reasonable because the IHT-XGB model is built on this original dataset. Table 4 also shows the prediction performance of five models, i.e., SSWRF, LORIS, PSIVER, SCRIBER, and DELPHI, in identification of protein-protein interaction sites [31][32][33][34][35][36][37]. The highest results in each performance measures for different models are highlighted as bold type.…”
Section: Prediction Performance In Independent Benchmark Datasetsmentioning
confidence: 99%
“…See Appendix K for additional discussion. scheme used by [15] (available at: https://github.com/CSUBioGroup/DeepPPISP). Table A1 shows the numbers of interaction and non-interaction sites in these datasets and the splits used in this study and [15].…”
Section: Discussionmentioning
confidence: 99%
“…As examples, we make available two graph-based protein structure datasets. The first, based on the collections outlined in (Zeng et al, 2019), consists of 420 proteins, with node labels indicating whether a residue is involved in a protein-protein interaction. The interaction status data and structure originate from structures of the complexes in the RCSB PDB.…”
Section: Datasetsmentioning
confidence: 99%